Showcasing a digital twin for higher educational buildings: developing the concept toward human centricity - Bäcklund, Katarina; Lundqvist, Per; Molinari, Marco (Frontiers in Built Environment, 2024)
Digital twin technology is an emerging technology within the built environment. There are yet many unexplored opportunities to utilize digital twins for facilitating the transformation towards a climate neutral building stock while also meeting the expectations from the building occupants. This article presents a case study of a digital twin, developed for an existing commercial building stock of campus areas in Sweden. The overarching purpose of the digital twin is to support both building occupants and building operators. This twofold human-centric approach represents a novel approach for building digital twins. The digital twin is based on 3D scanning and together with geospatial data, a real-like navigational indoor environment is created. Three innovative features are presented; the building analysis module, the digital twin mobile application and the building operations module. The results show that the digital twin improves the building occupant’s experience by supporting navigation and providing access to room booking system via this dedicated interface. Building management is also benefited by the digital twin through easier access to building data aggregated into one platform and a state-of-the-art analysis tool for optimizing the use of indoor space. The digital twin holds future potential to achieve operational excellence by incorporating feedback mechanisms and utilizing Artificial Intelligence to enable intelligent fault detection and prevention.